Pelatihan Media Google Classroom Pembelajaran Bahasa dan Sastra Indonesia bagi Kelompok Guru Bahasa Sekolah Menengah Pertama (SMP) - Dewi, Anita Candra; Ma’ruf (JPM (Jurnal Pemberdayaan Masyarakat), 2021)
This activity aims to introduce and provide new understanding to teachers about the importance of using google classroom media in learning Indonesian. The solution offered in this activity is to conduct training for teachers at SMPN 2 Tanete Rilau, Barru Regency, South Sulawesi Province, in the form of understanding the material and applying the google classroom media. The results of the interview show that teachers are still minimal to be creative in teaching online during this Covid-19 pandemic which has almost spread throughout Indonesia. Another result of this training activity is that the training participants consisting of Indonesian language teachers plus teachers from other fields of study have knowledge about the importance of google classroom during the covid 19 pandemic, participants are able to design classes through google classroom, and participants can manage classes during the Covid-19 pandemic. learning process using google classroom.